Rheology of microplatelet suspensions - Lim, Fiske Jie (Nanyang Technological University, 2021)
Mechanical properties of ceramic microplatelet reinforced composites can be tuned by manipulating the orientation stacks of microplatelets. Thus, to achieve this, the suspensions of such microplatelets need to be explored. The objective of this report is to understand microplatelet suspension rheology and the possibilities of usage for additive manufacturing. Microplatelets suspensions will be prepared in different concentrations as well as microplatelets with different aspect ratios. Rheology study will be done through rheological testing methods such as viscometry test and oscillatory test through a rheometer. Results will then be analyzed and discussions of critical factors for reaching the objectives and recommendations will be made through research from the literature review.